PEMBERDAYAAN MASYARAKAT DALAM BUANG AIR BESAR MELALUI METODE STBM DI RW. 07 PASIRKALIKI CIMAHI UTARA (Poltekkes Kemenkes Bandung, 2023)
Open defecation behavior still occurs in RT. 02 and 03 (RW. 07), Pasirkaliki Village, North Cimahi District, Cimahi City. Some residents of the community do not have a septic tank, they immediately throw their feces into the sewer. The goal is to find out the aspects of knowledge and aspects of community behavior RT. 02 and 03 Pasirkaliki Village, Cimahi City before and after community service, and the installation of 1 septic tank. The target is an increase in knowledge scores and changes in community behavior, as well as the installation of one piece septic tank. The outputs are: National Journal, Booklet and IPR, as well as the implementation video. The implementation method includes preparation, namely coordination with related parties, management of RT, RW, and Puskesmas permits, preparation of questionnaires, preparation of materials for counseling. The implementation includes: socialization to RT, RW, cadre and community managers, pretest, counseling, postest, RT, and RW deliberations, and community empowerment through septic tank construction. The partners are the people of RT. 02 and 03 Pasirkaliki Village, Cimahi City. The results achieved: there was an increase in the knowledge score of the RT. 02 and 03 community on average by 44%, there was a change in community behavior by 33.33%, and the installation of 1 septic tank. Outputs in the form of national journals, booklets and IPR, as well as implementation videos. Suggestion: The Pasirkaliki Health Center must be more intensive in conducting counseling about Stop Open Defecation (BABS) in RT. 02 and RT 03, must be more intensive in socializing about saving organic waste because not all people have participated in saving waste to build septic tanks, the community must participate in “Goyang Gotik” activities (gotong royong untuk membangun tangki septik) by saving inorganic waste, to assist in the manufacture of septic tanks.